Why do people take part in atrial fibrillation screening? qualitative interview study in English primary care - Hoare, S; Powell, A; Modi, RN; Armstrong, N; Griffin, SJ; Mant, J; Burt, J; Hobbs, F (BMJ Publishing Group, 2022)
Objectives: There is insufficient evidence to support national screening programmes for atrial fibrillation (AF). Nevertheless, some practitioners, policy-makers and special interest groups have encouraged introduction of opportunistic screening in primary care in order to reduce the incidence of stroke through earlier detection and treatment of AF. The attitudes of the public towards AF screening are unknown. We aimed to explore why AF screening participants took part in the screening.